(untitled) (Advancements in Homeopathic Research, 2020)
The concept of the terminology “Pharmacovigilance” now-a-days evolves, in the fields of Public Health System, greater importance inasmuch as it is bestowed with important inherent functions like describing the process for evaluating and monitoring Adverse Drug Reactions. It is undeniably a basic, prime and key component of proper and effective Regulatory System relating to Drugs, Public Health System as well as Clinical practice. Herein lays the veracity, importance and applicability of Pharmacovigilance in the Public Health System in specific, being the effective Monitoring System in greater perspectives. The word “Pharmacovigilance” have two parts. The first part or portion being the word ‘Pharmaco’ derives from the Greek word and term ‘Pharmakon’, which means Medical Substances and the concluding portion thereof being ‘vigilance’ derives from the Latin term ‘Vigilia’, which means to keep watch. Pharmacovigilance is an important and integral part of clinical research and it plays a key role in the Healthcare System through assessment, monitoring and discovery of interactions amongst drugs and their effects in human. It is true that Biotechnological and/or Pharmaceutical Medicines, being manufactured, are basically, solely and mainly for treating, curing and preventing the diseases. Yet, it is often found that there are Adverse Drug Reactions and also risks in the application, consumption and medication of some of such Medicines, causing harm to patients. These, mainly for safe medication, warrant monitoring of Medicine right from the early stages of drug design and its Clinical Trial at its pre-marketing stage and also post marketing surveillance throughout its life cycle to ascertain, detect and prevent the Adverse Drug Reactions of the same, if be any. These coveted functions are the scopes of concern for Pharmacovigilance as it is to detect, assess understand and prevent the Adverse Drug Reactions (ADRs). These apart, Misleading Advertisements and/or negative effects of false advertising have, in the recent past, been on the rise to attract customers to rack up as many profits as possible with a view to buying a service or product as assured therein are very much unethical, as in practice, they overshadow or contradict the truth about the product or service. The object of Pharmacovigilance is here to policing, preventing and very much committed to take appropriate actions against those errant Advertisers to keep the interest of members of general public protected at large since misguided customers will end up wasting valuable money, in return of which they really won’t meet their needs or solve their problems; ultimately.